Open Government in Authoritarian Regimes - Karl O’Connor; Saltanat Janenova; Colin Knox (International Review of Public Policy)
Open government has long been regarded as a pareto-efficient policy – after all, who could be against such compelling policy objectives as transparency, accountability, citizen engagement and integrity. This paper addresses why an authoritarian state would want to adopt a policy of open government, which may first seem counter-intuitive, and tracks its outworking by examining several facets of the policy in practice. The research uncovers evidence of insidious bureaucratic obstruction and an implementation deficit counter-posed with an outward-facing political agenda to gain international respectability. The result is ‘half-open’ government in which the more benign elements have been adopted but the vested interests of government and business elites remain largely unaffected.